9.CORNEAL ENDOTHELIOPATHY IN PSEUDOEXFOLIATION SYNDROME (Iraqi Journal of Medical Sciences, 2018)
Background: Pseudoexfoliation syndrome is a common disorder with a wide range of ophthalmic presentation and risks. Corneal endotheliopathy is one of these presentations.Objective: To evaluate corneal endothelial cell morphology, density and function in eyes with pseudoexfoliation syndrome.Methods: 120 eyes of sixty patients with clinically evident unilateral pseudoexfoliation were examined with non-contact specular microscopy (SP-3000P) Topcon Corporation. Central corneal thickness (T), cell density (CD), and percentage of cell hexagonality (HEX%) were measured and the values of the affected eyes were compared to those of the fellow normal eyes. Corneas with CD less than 2000/mm2 or HEX%
Keywords: Pseudoexfoliation; corneal endothelium; endotheliopathy; decompensation